Relationship between Internet Addiction and Depression among Secondary School Students in Kordkuy, Iran, with an Emphasis on the Type of Virtual Network - Ebrahim Salehi Omran; Meymanat Abedini baltork; Mostafa Azizi Shomami; Kosar Keshavarz (Hamadan University of Medical Sciences, 2018)
Background and Objective: The internet can sometimes endanger the users' mental health due to its improper use. Accordingly, this communication network has turned into an addictive factor in recent decades. This kind of addiction can lead to depression. Regarding this, the present study was conducted to determine the relationship between internet addiction and depression among secondary school students. Materials and Methods: This descriptive and correlational study was conducted on secondary school students in Kordokuy city, Golestan, Iran, in the academic year of 2016-2017. The sample size was determined as 288 cases based on the Morgan sampling table. The study population was selected using cluster sampling method. The data were collected using the Beck Depression Inventory and Internet Addiction Inventory by Young. Data analysis was performed in SPSS (version 21) using independent t-test, one-way ANOVA, and Spearman's correlation coefficient. Results: According to the results, there was a direct relationship between addiction to internet and students' depression (r=0.324, P<0.001). The largest use of virtual networks was related to Telegram software with the mean value of 40.29. Furthermore, no significant difference was observed between the male and female students in terms of internet addiction and depression (P>0.05). Conclusion: Given the significant relationship between the internet addiction and depression among students, it is recommended to design and implement educational programs for students and parents.